Religious moderation in the glorious era (reality of religious tolerance and protection during the Ottoman Empire) - Sidqi, Kholfan Zubair Taqo; Zulfa, Laila Ngindana; Larhzizer, Fouad (IAIN Salatiga, 2023)
This research aims to find out that during the reign of the Ottoman Empire there was inter-religious tolerance. There were even concrete contributions from Turkish Sultans respecting followers of other religions, providing protection for Christians and Jews who were hit by bloody conflicts. Several areas of the Turkish Sultanate allowed residents of different religious beliefs to live. Through the social structure that has been created by Muslim, Christian and Jewish citizens can live together in peace and tranquility. The research method is carried out by collecting information and data of various kinds of materials in the library such as reference books, results of similar previous research, articles, notes, and various journals related to the problem. The results are that the reality of religious tolerance and protection of non-Muslims during the Ottoman era was implemented well, especially since there was the al-Qanun law which generally regulated the legal system for its territory with an emphasis on the benefit of the ummah. There is also a Millet System that specifically regulates Muslims and non-Muslims living peacefully. The fact that the conquest of Constantinople did not destroy places of worship, nor did it force the conquered people to convert to Islam.